Association between El Niño and extreme temperatures in southern South America in CMIP5 models. Part 2: future climate projections - Collazo, Soledad Maribel (2021)
This study provides an overview of projected future changes in the probability density function (PDF) and variability of the equatorial Pacific sea surface temperature in the El Niño 3.4 region (SST3.4). We analyzed how these changes affect the relationship with extreme temperature events in southern South America under global warming. We used 2 different emission scenarios for climate change simulations in the Coupled Model Intercomparison Project Phase 5 (CMIP5): RCP4.5 and 8.5, and for 2 future periods: 2031-2060 and 2071-2100. The Kolmogorov-Smirnov test was applied to compare the PDFs of SST3.4 between historical and future periods. We found that the PDFs of SST3.4 for both future periods differed significantly from the PDFs of the historical period for both scenarios. Changes in SST3.4 under greenhouse warming will alter the intensity and position of the teleconnection patterns. In particular, we observed that the mean difference in sea level pressure anomalies between El Niño and La Niña will weaken in the future. This result could explain why, in general, no significant correlations or quantile regressions were projected between SST3.4 and extreme temperature indices in southern South America for both the near and far future. The projections of the best-performing models in the historical period did not provide much clarity because they differ from each other but showed us that the individual models simulate changes in the relationships between SST3.4 and extremes temperature according to the period and scenario.